Technology-Supported Professional Learning for Mathematics Teachers: Insights from Bibliometric Analysis and Systematic Literature Review - Winarti, Wiwin Eka (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
The rapid advancement of educational technology has transformed teacher professional learning from conventional training models toward technology-supported, collaborative, and continuous learning ecosystems. This study aims to map global research trends on technology-supported professional learning for mathematics teachers, identify major thematic developments through bibliometric analysis and systematic literature review, and formulate implications for strengthening professional learning communities in mathematics education. A combined bibliometric and systematic literature review approach was employed using the Scopus database. A total of 230 journal articles published between 2018 and 2025 were analyzed bibliometrically, while 25 core studies were selected for in-depth thematic synthesis. Bibliometric mapping revealed a consistent increase in publications and identified dominant contributions from countries and institutions with well-established educational research ecosystems. Keyword co-occurrence analysis highlighted four interconnected themes: mathematics teacher competencies, technology-supported professional development, collaborative classroom-based learning practices, and mathematics teacher education. The systematic synthesis further demonstrated that effective professional learning is characterized by sustained collaboration, reflective practice, classroom relevance, and increasing integration of digital technologies, artificial intelligence, video-based learning, and technology-enhanced professional learning communities. These findings indicate a growing shift toward technology-supported professional learning ecosystems that enable teachers to strengthen instructional practices, foster higher-order thinking, and support deep learning implementation. The study contributes to the field of educational technology by providing evidence-based insights into how mathematics teacher professional learning can be redesigned through technology integration and offers practical directions for transforming Mathematics Teacher Working Groups (MGMP) into technology-responsive professional learning communities capable of supporting sustainable instructional innovation.